Food sovereignty and rural development: beyond food security (2013)
Food sovereignty and food security are not the same issue. Both are different but many people around the world confuse the two. This article explores and analyzes the issues surrounding food security and food sovereignty in order to explain the differences between them, identifies the principal statements in food sovereignty and compares some data from different countries in an attempt to highlight the fact that food security policies result in hunger, poverty and environmental damage. Food security and rural development share similar goals, both seek to improve the quality of life of peasants and rural inhabitants; however, economic ideas are unfortunately still prized more than people.